Trend of Fast Food Consumption among University Students of Karachi - Shanila Faisal, Muhammad Adnan Kanpurwala, Shamsul Arfin Qasmi, Hina Riaz, Asima Faisal (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objectives: The purpose of this paper is to assess the frequency of fast food consumption, the factors which lead to its consumption and the awareness of its health effects among university students of Karachi. Place & Duration: Descriptive cross sectional study conducted in Karachi, Pakistan. The target populatin includes university students enrolled in the management programs (BBA & MBA) of Iqra University & Institute of Business Management, Karachi, during May 18.2013 to August 18, 2013. Material & Methods: A descriptive cross sectional study was conducted using self-administered questionnaire. 100 students were selected through convenient sampling from the management departments of two private universities of Karachi and data was collected after taking informed consent from them. Results: The results of the study have shown that around 97% of the university students consume fast food meal out of which 44% of them consumed it 2-3 times every week. The most appealing factor for the selection of fast food was the taste as reported by 63% of the students and 66% of the students preferred to purchase food from the branded restaurants. Majority of the students were also have some idea about the nutritional values of the food and 54").•’of them were of the opinion that the fast food is a risk factor for obesity. Conclusion: Although the students are aware of the nutritional information of the fast food and the health hazards related to it to some extent such as obesity, hypertension etc they still prefer to consume it regularly. Therefore there is a strong need to give more detail awareness about the effects of fast foods on their health in order to promote a healthy society.